DETERMINANTS OF ECONOMIC AND ENVIRONMENTAL FACTORS ON THE INCOME OF COCONUT FARMERS IN SIMEULUE REGENCY - Affandi Affandi; Ilfan Fakhri; Harmaini Harmaini; Sudarman Sudarman; Rina Farah (Scientechno: Journal of Science and Technology, 2026)
This study aims to examine the economic and environmental determinants of coconut farmers’ income in Simeulue Regency by analysing land area, selling price, labour, and damaged trees as independent variables, with farmers’ income as the dependent variable. This study employs a quantitative method based on multiple linear regression analysis of primary data collected through questionnaires and interviews with 97 coconut farmers selected using the Slovin formula, supplemented by secondary data from relevant institutions. The results indicate that all variables simultaneously influence farmers’ income; however, when analysed individually, land area and labour have a positive and significant effect, the selling price shows a positive effect, and damaged trees have a negative but non-significant impact on income levels. These findings imply that owning larger landholdings and utilising labour efficiently can help increase farmers’ income, whereas pest-damaged trees remain a major challenge for boosting productivity. Therefore, efforts such as improving land management, optimising labour use, maintaining price stability, and implementing sustainable pest control are crucial for improving the welfare of coconut farmers in Simeulue Regency.